Development of Volleyball Match Statistics Applications - Pratama, Galih; wahyudi, agung; Nasuka, Nasuka (Universitas Negeri Semarang, 2025)
The purpose of this research is to create a volleyball match statistics application and determine the effectiveness of the product. The research method used is research and development. Before the product trial, this product has been validated by volleyball experts and media experts. The assessment conducted by volleyball experts received an average score of 86.7% with